IMPACT OF ROAD INFRASTRUCTURE, EDUCATION, HEALTH AND FOREIGN DIRECT INVESTMENT TOWARDS INDONESIA’S ECONOMIC GROWTH: LEVEL OF 33 PROVINCES - Muryani Muryani; Agna Amalia (AFEBI Economic and Finance Review, 2018)
Economic growth is the most important factor to gain successful long-term development. The economy growth factors are road infrastructure, education, health, and foreign direct investment. This study analyzes the influence of road infrastructure, education, health and foreign direct investment on economic growth of 33 provinces in Indonesia in 2010-2016. This study uses panel data regression method and uses STATA 14 software. The regression estimation results showed that simultaneously road infrastructure, education, health, and foreign direct investment had an effect on economic growth of 33 provinces in Indonesia, while partially (individually) foreign direct investment doesn’t have significant effect.JEL Classdification: H51, H52, H54Keywords: Economic Growth, Education, Foreign Direct Investment, Health, Road Infrastructure